1995
DOI: 10.1136/oem.52.8.534
|View full text |Cite
|
Sign up to set email alerts
|

Impaired colour discrimination among workers exposed to styrene: relevance of a urinary metabolite.

Abstract: Objectives-To survey the loss of colour vision among Japanese workers who have been exposed to styrene concentrations currently considered low (about 20 ppm). Also to assess the effects of styrene by examination of the nature of the relation between disorder of colour vision and age, alcohol consumption, and other variables. Methods-Colour discrimination was examined in 64 male workers exposed to styrene (mean age; 38'0, mean exposed years; 7'0) and in 69 controls (mean age; 38.0). A standardised questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…The published studies often take the length of service or duration of exposure into consideration as a re¯ection of the past. Several authors [5,8,10] who included this indicator in their regression models found no signi®cant link with the CCI, whereas they did ®nd one with current exposure. Most, however, took the precaution of carrying out the tests at the beginning of a period of exposure so as to avoid the eects of subacute exposure.…”
Section: Discussionmentioning
confidence: 85%
“…The published studies often take the length of service or duration of exposure into consideration as a re¯ection of the past. Several authors [5,8,10] who included this indicator in their regression models found no signi®cant link with the CCI, whereas they did ®nd one with current exposure. Most, however, took the precaution of carrying out the tests at the beginning of a period of exposure so as to avoid the eects of subacute exposure.…”
Section: Discussionmentioning
confidence: 85%
“…The previous threshold limit of exposure to styrene was 50 ppm in the U.S.A. (until 1997) and Japan (until 1999). However, even exposure to concentrations lower than this limit, might lead to the impairment of color vision 15,17,18) . Some researchers examined the dose response, and found that styrene could induce dose-dependent color vision loss 15,16,18) .…”
Section: Results Of Previous Studiesmentioning
confidence: 99%
“…The results of these studies showed that such impairment often occurred among the workers exposed to styrene ( Table 4). The interrelationship between the degree of exposure to styrene and the impairment of color vision was investigated 6,[15][16][17][18][19] . The previous threshold limit of exposure to styrene was 50 ppm in the U.S.A. (until 1997) and Japan (until 1999).…”
Section: Results Of Previous Studiesmentioning
confidence: 99%
“…Acquired dyschromatopsia has been associated with exposure to mixtures of solvents, n-hexane, styrene, perchloroethylene, and carbon disul®de (Alieva et al 1985;Braun et al 1989;Campagna et al 1995;Cavalleri et al 1994;Chia et al 1994;Eguchi et al 1995;Fallas et al 1992;Mergler et al , 1988Mergler et al , 1990Raitta et al 1978Raitta et al , 1981. In contrast to the congenital form, acquired dyschromatopsia is not a clinical diagnosis but a symptom mostly caused by diseases of the retina and/or the optic nerve.…”
Section: Introductionmentioning
confidence: 97%